DNase II activated by the mitochondrial apoptotic pathway regulates RIP1-dependent non-apoptotic hepatocyte death via the TLR9/IFN-β signaling pathway - Saito, Yoshinobu (Cell Death Differ, 2018)
Cell death, including apoptotic and non-apoptotic cell death, is frequently observed in liver disease. Upon activation of the mitochondrial apoptotic pathway, mitochondria release not only apoptogenic cytochrome c but also mitochondrial DNA (mtDNA) into the cytosol. The impact of DNase II, a lysosomal acid DNase that degrades mtDNA, on hepatocyte death remains unclear. Administration of ABT-737, a Bcl-xL inhibitor, upregulated DNase II activity in murine hepatocyte cell line BNL CL.2 cells and induced apoptosis. In cells treated with DNase II siRNA, ABT-737 led to accumulation of mtDNA in the cytosol and increased expression of interferon (IFN)-β and induction of propidium iodide (PI)-positive cells, in addition to apoptosis. Induced PI-positive cells were suppressed by RIP1 inhibitor, Necrostatin-1, but not by pan-caspase inhibitor, ZVAD-FMK, suggesting non-apoptotic cell death. Both the increase in IFN-β and the induction of non-apoptotic cell death were abolished by administering a TLR9 antagonist, ODN2088, or by the removal of mtDNA from cells with ethidium bromide. Hepatocyte-specific Mcl-1 knockout mice developed hepatocyte apoptosis accompanied by upregulated DNase II activity in their livers. Further knockout of DNase II induced IFN-β expression and RIP1-dependent non-apoptotic hepatocyte death, both of which were suppressed by the administration of ODN2088. Mice fed a high-fat diet (HFD), an obesity-associated fatty liver model, showed increased expression of IFN-β with suppression of DNase II activity in their livers and developed not only hepatocyte apoptosis but also non-apoptotic hepatocyte death. Hepatocyte-specific knockout of DNase II exacerbated HFD-induced non-apoptotic hepatocyte death and liver fibrosis. In conclusion, without DNase II, apoptotic stimulation on hepatocytes induces TLR9-dependent IFN-β production and RIP1-dependent non-apoptotic cell death originating from mtDNA. In fatty livers, DNase II activity is suppressed in contrast to simple inactivation of Bcl-xL or Mcl-1, and both apoptotic and non-apoptotic hepatocyte death can develop, leading to the progression of liver fibrosis.